Wireless Integrated System for Efficient Restaurant with bluetooth (WISERbt) / Raja Zulfiz Raja Zahabuddin - Raja Zahabuddin, Raja Zulfiz (Faculty of Information Technology and Quantitative Sciences, 2006)
The main purpose of this project is to upgrade the previous system that uses Window XP, Access Point, Wireless Card, and HP iPAQ Pocket PC. The new system will be upgraded with the Bluetooth technology that enable user to communicate with each other using Bluetooth. A prototype of the system that is Wireless Integrated System for Efficient Restaurant with Bluetooth (WISERbt) that combines the Bluetooth technology using affordable Point-of-Sales (POS) software, PDA’s, Bluetooth enabled hand phones, and other peripherals is developed.